Factors affecting the efficiency of management in admitting students to further studies Bachelor’s degree of the Northern Vocational Education Institute 4. - Thongdee, Saptasorn (Journal of Humanities and Social Sciences, Rajapruk University, 2025)
This research aimed to (1) study the level of opinions regarding the efficiency of undergraduate student admission management at Northern Vocational Education Institute Region 4, (2) compare opinions on the efficiency of such management classified by personal factors, and (3) examine factors influencing the efficiency of undergraduate student admission management. The sample consisted of 234 administrators, government teachers, and educational personnel selected using stratified sampling. The research instrument was a questionnaire with content validity (IOC ≥ 0.50) and overall reliability of 0.978. Data were analyzed using descriptive statistics (frequency, percentage, mean, and standard deviation), and inferential statistics including t-test, one-way ANOVA with LSD for pairwise comparisons, and multiple linear regression analysis. The findings indicated (1) generally high perceptions of management efficiency among staff, (2) significant statistical differences in perceptions based on age, seniority, and position, and (3) contributing factors included values, strategies, skills, systems, and structures, which explained 84.70% of the management efficiency variance. Predictive equations were provided in raw score (Y = .420 +.308X7 +.099X2 +.252X4 +.143X3 +.112X1) and standardized score (Z = .314X7 +.136X2 +.254X4 +.183X3 +.139X1)